2015
DOI: 10.1186/s13014-014-0312-5
|View full text |Cite
|
Sign up to set email alerts
|

Intensity modulated radiotherapy for locally advanced and metastatic pancreatic cancer: a mono-institutional retrospective analysis

Abstract: BackgroundTo evaluate the role of intensity modulated radiotherapy (IMRT) for locally advanced pancreatic cancer (LAPC) and metastatic pancreatic cancer (MPC), and the prognostic factors in the setting of multidisciplinary approach strategies.Methods63 patients with LAPC and MPC receiving IMRT in our institution were retrospectively identified. Information on patient baseline, treatment characteristics and overall survival (OS) time were collected. Data of pain relief and toxicity were evaluated. Univariate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…Wang et al . in their study reported decrease in pain intensity in 44 of the 63 (70%) patients who received intensity modulated radiation therapy . Similar results are presented in another article in which an effectiveness of stereotactic body radiotherapy using CyberKnife was evaluated .…”
Section: Chemotherapy and Radiotherapysupporting
confidence: 73%
“…Wang et al . in their study reported decrease in pain intensity in 44 of the 63 (70%) patients who received intensity modulated radiation therapy . Similar results are presented in another article in which an effectiveness of stereotactic body radiotherapy using CyberKnife was evaluated .…”
Section: Chemotherapy and Radiotherapysupporting
confidence: 73%
“…However, this treatment has a low response rate and increases the risk of severe side effects, including cytopenia and bone marrow suppression (30,31). Arterial infusion, including RIAC, has been used as an alternative strategy to increase the survival rates for patients with pancreatic cancer (19,30,32). RIAC delivers a high concentration of drugs into the artery connected to the tumor and provides patients an optimal therapeutic approach, particularly for APC (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…RIAC delivers a high concentration of drugs into the artery connected to the tumor and provides patients an optimal therapeutic approach, particularly for APC (33,34). Although RIAC is not a routine treatment for pancreatic cancer, clinical trials have identified that RIAC achieves a significant benefit in terms of overall survival rates and symptomatic control in patients with pancreatic cancer (5,32).…”
Section: Discussionmentioning
confidence: 99%
“…First, we carried out treatment planning by using a 3D-CRT technique, whereas intensity-modulated radiotherapy is being used increasingly for patients with pancreatic cancer. 23 Second, the accuracy of the conversion into the RED and the MD using the WDI was investigated for 15 mg/mL iodine at the maximum density in the phantom study; however, the iodine density in patients may be larger at the aorta and kidneys, which are strongly enhanced by the contrast-enhancing agent in the pancreatic phase image. Thus, our phantom study could not assess the accuracy of the conversion of the WDI to the RED and the MD for iodine material >15 mg/mL.…”
Section: Discussionmentioning
confidence: 99%